2015
DOI: 10.1007/s10616-015-9913-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of factors influencing extracellular vesicle yield from cell cultures

Abstract: The potential therapeutic utility of extracellular vesicles (EVs) has spawned an interest into a scalable production, where the quantity and purity of EV samples is sufficient for clinical applications. EVs can be isolated using several different protocols; however, these isolation protocols and the subsequent methods of quantifying the resulting EV yield have not been sufficiently standardized. Therefore, the possibility of comparing different studies with respect to these parameters is limited. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 89 publications
2
91
1
Order By: Relevance
“…In the present study, ASC exosomes were shown to be devoid of any proliferation-stimulating properties after 4 days on two different GBM cell lines, including a cancer stem cell line, underscoring their relevance with respect to safety in delivering therapeutics to GBM tumors. However, for ASC (or any other cell type's) exosomes to be used in any sort of therapy, one would also need to include a thorough assessment of how the cell culture conditions affect the production and characteristics of the secreted exosomes (Gudbergsson et al 2015). For example, several types of cell stress, such as hypoxia, cell activation and high glucose, are known to interfere with the released quantity of exosomes, but also with their composition of proteins and RNA, whereas the effects of other components of cell culture, like the surface structure of the culture dish, remain completely unknown (de Jong et al 2012;King et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, ASC exosomes were shown to be devoid of any proliferation-stimulating properties after 4 days on two different GBM cell lines, including a cancer stem cell line, underscoring their relevance with respect to safety in delivering therapeutics to GBM tumors. However, for ASC (or any other cell type's) exosomes to be used in any sort of therapy, one would also need to include a thorough assessment of how the cell culture conditions affect the production and characteristics of the secreted exosomes (Gudbergsson et al 2015). For example, several types of cell stress, such as hypoxia, cell activation and high glucose, are known to interfere with the released quantity of exosomes, but also with their composition of proteins and RNA, whereas the effects of other components of cell culture, like the surface structure of the culture dish, remain completely unknown (de Jong et al 2012;King et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[ 150 nm) could also be detected. It should be noted that the distinction between different types of EVs cannot solely be based on their size distribution, as some level of diameter overlap will be expected (Gudbergsson et al 2015). The total yield of EVs from the CM was found to be high, averaging around 6 9 10 10 particles/T175 culture flask (Fig.…”
Section: Adipose-derived Stem Cells Are Efficient Producers Of Extracmentioning
confidence: 96%
See 2 more Smart Citations
“…Ultracentrifugation-free methods for isolation of EVs have also been developed, including ultra-filtration, precipitation and immuno-affinity capture using specific antibodies. Although studies have investigated factors affecting the efficiencies of these methods [1316], there is no study comparing the biological activities of the EVs isolated by these methods.…”
Section: Introductionmentioning
confidence: 99%